2001
DOI: 10.1080/09637480120057558
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coronary risk factors in healthy adult Kuwaitis

Abstract: Obesity has been shown to be a serious health risk and is associated with a wide range of comorbid conditions, including diabetes mellitus, coronary heart disease (CHD), gall bladder disease, hypertension, osteoarthritis, and certain cancers. Studies in Kuwait and other Gulf States indicate that obesity is prevalent and may be increasing. Previous studies in Kuwait have mostly focused on the epidemiology of overweight and obesity in children, adolescents, and young adults. Relatively less is known about the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Furthermore, of all studies reviewed (including those of random blood glucose and impaired fasting glucose), five considered the effect of age on prevalence. 4244,49,50 All found the prevalence was higher with advancing age, and in all cases where tested (three cases), the relationship was found to be significant. 43,49,50 …”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…Furthermore, of all studies reviewed (including those of random blood glucose and impaired fasting glucose), five considered the effect of age on prevalence. 4244,49,50 All found the prevalence was higher with advancing age, and in all cases where tested (three cases), the relationship was found to be significant. 43,49,50 …”
Section: Resultsmentioning
confidence: 74%
“…Five studies were carried out (where reported) and/or published in the late 1980s, 23 in the 1990s, and 15 in the last 10 years. Studies of various 20 Saudi, 24–46 , seven Kuwaiti, 4750 three Bahraini, 5153 eight Emirati, 5460 four Omani 6164 and one Qatari 65 populations were included. All were cross-sectional studies; 23 of the general population, seven of primary care populations, four of schoolchildren, three of students, one of a young population, five of working populations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[35] An estimated one-third of Kuwaiti adults are obese- and there have been several reports describing the pervasiveness of childhood and youth obesity in varying age groups. [3] Rapid modernization leading to changed dietary and physical activity patterns is often hypothesized to be the primary catalyst in Kuwait's obesity epidemic [2, 4, 5]. It is essential to learn more about prevalence, predictors, associated risk factors, and prevention of childhood/adolescent obesity in Kuwait.…”
Section: Introductionmentioning
confidence: 99%